A Linear Regression Equation for Predicting the Residual Volume of Chronic Subdural Hematoma 1 Week After Surgery - Yan C; Su C; Ye YF; Liu J (Neuropsychiatric Disease and Treatment, 2023)
Chao Yan,1,* Chang Su,1,* Yu-fei Ye,2 Jin Liu1 1Department of Neurosurgery, the Sixth Affiliated Hospital of Wenzhou Medical University, Lishui, Zhejiang, 323000, People’s Republic of China; 2Department of Neurosurgery, Qingyuan People’s Hospital, Lishui, Zhejiang, 323800, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jin Liu, Department of Neurosurgery, the Sixth Affiliated Hospital of Wenzhou Medical University, 1188 Liyang Street, Liandu District, Lishui, Zhejiang Province, 323000, People’s Republic of China, Email Liujin614@lsu.edu.cnObjective: The outcome of chronic subdural hematoma (CSDH) is influenced not only by the choice of treatment but also by various baseline characteristics. The main objective of this study is to identify the risk factors that can affect the prognosis of CSDH and develop a regression equation based on these risk factors.Methods: A total of 212 patients with CSDH were included in the study. We collected clinical data including age, gender, and so on, and radiological data including preoperative hematoma volume (V1), effusion volume 1 day after surgery (V2), gas volume 1 day after surgery (V3), and so on. These were considered independent variables, while residual volume 1 week after surgery (V4) was the dependent variable. Univariate linear regression analysis was performed to identify factors that were significantly related. Subsequently, multivariate linear regression analysis was conducted to determine the relationship between each independent variable and the dependent variable. Multiple linear regression analysis was used to obtain a regression equation predicting V4.Results: We have found that age (t = 3.109, P = 0.002), aspirin (t = 2.762, P = 0.006), hemostatic agents (haemocoagulase, t = 3.731, P < 0.001; vitamin K, t = 2.824, P = 0.005 < 0.05), V2 (t = 8.73, P < 0.001), and V3 (t = 5.968, P < 0.001) are significantly associated with V4. Furthermore, we have developed a regression equation that can predict this volume with CSDH. The fit of the model is robust with an R-squared value of 65.2% > 50%.Conclusion: Age, aspirin, hemostatic agent, V2, and V3 are significantly associated with V4. We developed a regression equation to predict this volume with CSDH.Keywords: CSDH, burr-hole and drainage, regression equation